Fiscal allotment policy vis a vis minorities - Shahor, Tal (Metodološki zvezki, 2010)
This paper examines government attitudes to minorities in multinational countries. The aim is to present a procedure that empirically measures government attitude to the minority sector of the population on matters relating to fiscal allotments. The paper applies the proposed procedure to the current situation in Israel, and examines whether the Israeli Government, which is dominated by the Jewish majority, adopts a policy of affirmative action to benefit the Arab minority. The study will examine this question within the parameters of local government. The general trend evident in the results of this study shows an increase in fiscal allotments transferred to Arab sector local authorities. Furthermore, results show that in the years 2006 and 2007 there was no significant difference between Arab and Jewish local authorities in the same socio-economic characteristics and the same peripheral level.
Keywords: Government policy; Vladna politika; Fiscal policy; Fiskalna politika; Manjšine; Minorities; Arab; Arabci; Arabs; Israel; Izrael; narodne manjšine; tax; davki; davčna politika